2016
DOI: 10.1016/j.ajhg.2016.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in GLDN , Encoding Gliomedin, a Critical Component of the Nodes of Ranvier, Are Responsible for Lethal Arthrogryposis

Abstract: Arthrogryposis multiplex congenita (AMC) is a developmental condition characterized by multiple joint contractures resulting from reduced or absent fetal movements. Through linkage analysis, homozygosity mapping, and exome sequencing in four unrelated families affected by lethal AMC, we identified biallelic mutations in GLDN in the affected individuals. GLDN encodes gliomedin, a secreted cell adhesion molecule involved in the formation of the nodes of Ranvier. Transmission electron microscopy of the sciatic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 18 publications
(26 reference statements)
2
56
0
Order By: Relevance
“…Here, loss of the transverse bands resulted in paranodal myelin loop detachment and reduced conduction velocities 78. In mouse models mimicking CMT1A79 and 1C,80 paranodal structural changes, including loss of transverse bands and peeling back of myelin loops in the former, or myelin infolding in the latter, are shown to affect conduction and likely contribute to both the demyelination and axonal degeneration seen in these conditions.…”
Section: Neuropathies and The Paranodementioning
confidence: 90%
“…Here, loss of the transverse bands resulted in paranodal myelin loop detachment and reduced conduction velocities 78. In mouse models mimicking CMT1A79 and 1C,80 paranodal structural changes, including loss of transverse bands and peeling back of myelin loops in the former, or myelin infolding in the latter, are shown to affect conduction and likely contribute to both the demyelination and axonal degeneration seen in these conditions.…”
Section: Neuropathies and The Paranodementioning
confidence: 90%
“…Features variably included intrauterine growth retardation, knee and elbow contractures, camptodactyly and retrognathia 36. Electron microscopy of one patient’s sciatic nerve showed reduced numbers of myelinated fibres and a significant increase in nodal length.…”
Section: Genes Encoding Components Of the Peripheral Nervous Systemmentioning
confidence: 98%
“…Maluenda et al 36 identified six individuals with AMC, marked polyhydramnios and fetal akinesia at 27–32 weeks’ gestation, despite unremarkable earlier ultrasounds. Features variably included intrauterine growth retardation, knee and elbow contractures, camptodactyly and retrognathia 36.…”
Section: Genes Encoding Components Of the Peripheral Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the biallelic mutations found in the affected individuals of these four families are likely to cause defective signaling of the LGI4 pathway similar to that observed in Lgi4-deficient mice. Recent data indicate that mutations of genes encoding CASPR-1 19 and gliomedin, 20 essential components of the nodes of Ranvier and paranodes, respectively, or proteins involved in myelination of Schwann cells such as ADCY6 19 and GPR126, 21 are responsible for severe human peripheral axoglial diseases, resulting in developmental defect of PNS, hypokinesia, and arthrogryposis. Here, we show that loss-of-function germline mutations of LGI4 leads to a similar phenotype.…”
mentioning
confidence: 99%